Fiqh Reform in the Sultanate of Aceh Darussalam: Is it Modernism or Moderatism? A Study of the Hareuta Sihareukat Custom - Sabil, Jabbar; Faisal, Faisal; Zukhdi, Muhammad (SCAD Independent, 2025)
The custom of joint property in marriage exemplifies the Fiqh reform during the Sultanate of Aceh Darussalam. Some authors link this custom to the issue of women’s equality that strengthened in the 1970s. However, it raises questions about the paradigm that underlies this custom: Did the Acehnese ulema adhere to the same paradigm as modern thinkers? The authors hypothesize that the paradigm underlies this custom is moderate because it moderates between women’s property ownership dimension and the dimension of the family’s living needs. The primary data for this study are legal materials in the form of law books, regulations, and constitutions of Aceh Darussalam Sultanate. Therefore, the authors conducted normative legal research with a historical approach. The authors used Gadamer’s dialogical hermeneutics to moderate the subject and object as a dialogue partner. This study found that Acehnese ulema, who served as chairman of the Supreme Court (Qāḍi Mālik al-’Ādil), was moderate in Aqida, Sharia, and Siyasa, so the moderate paradigm influenced the law system in The Sultanate of Aceh Darussalam. It resulted in the fiqh reform, which means compatibility between the opinions of the ulemas and the needs of the people. It concluded that the fiqh reform carried out by the Acehnese ulema was moderation.